The Role of the Principal's Academic Supervision and Teacher Work Motivation in Improving Teacher Professionalism at SMKN 7 Manado - Sulastri Darise; Romi J. Mongdong; Roos M.S Tuera (International Journal of Information Technology and Education, 2026)
This study aims to analyze the influence of the principal's academic supervision and teacher work motivation on teacher professionalism, both partially and simultaneously, at SMK Negeri 7 Manado. This study used a quantitative approach with multiple linear regression analysis. The population and sample were all 38 teachers at SMK Negeri 7 Manado, using a census sampling technique. Data were collected through questionnaires and analyzed using the classical assumption test, t-test, F-test, and coefficient of determination (R²) using SPSS. The results showed that: (1) the principal's academic supervision had a significant effect on teacher professionalism with a significance value of 0.039 < 0.05, but with a negative direction of the effect, indicating that the implementation of supervision has not fully shifted from an evaluative paradigm to a continuous professional development approach; (2) teacher work motivation had a significant effect on teacher professionalism with a significance value of 0.026 < 0.05, with a negative direction of the effect reflecting the dominance of extrinsic motivation over intrinsic motivation in developing teacher professional competence; (3) The principal's academic supervision and teacher work motivation simultaneously have a significant effect on teacher professionalism, with a calculated F-value of 4.737 and a significance level of 0.015 < 0.05. The Adjusted R² value of 0.168 indicates that these two variables contribute 16.8% to the variation in teacher professionalism, while 83.2% is influenced by factors outside this research model. This study recommends transforming the academic supervision approach from an inspection model to a dialogic and reflective coaching model, as well as strengthening teacher intrinsic motivation by providing professional autonomy and creating a collaborative culture in the school environment.